QUANTUM LEARNING AS A NATURAL WAY TO IMPROVE STUDENTS’ LANGUAGE COMPETENCE - Ida Bagus Nyoman Mantra; Nengah Dwi Handayani; I Nyoman Suwandi (International Journal of Applied Science and Sustainable Development (IJASSD), 2019)
Quantum Education is the natural way to learn to motivate and excite students to take responsibility for their learning. In quantum learning, the environment of learning is prepared with didactic materials for the children to learn at their own learning pace. Students learn without formal pedagogical machinations, without consciously participating in the learning activities. The present study was conducted to attempt at improving students' language competence through quantum learning. The present classroom action study was triggered by the fact that the subjects under study still faced a problem in improving language competence. The present classroom action study made use of pre-test and post-test research design with descriptive and quantitative analysis. The grand mean figures for the first cycle and second cycle showed significantly increasing mean figures. The significant difference mean figure further suggests that the second cycle was more effective than the first cycle. The results of the analysis of the questionnaire scores clearly showed the students’ attitudes andmotivation in improving their language competence through quantum learning. Therefore, it could be concluded that quantum learning is an effective teaching model to improve the students’ language competence.